Integrated stratigraphy across the Aptian-Albian boundary in the Marnes Bleues, at the Col de Pre-Guittard, Arnayon Drome), and at Tartonne (Alpes-de-Haute-Provence), France: a candidate Global Boundary Stratotype Section and boundary point for the base of the Albian Stage - Kennedy, WJ; Gale, AS; Bown, PR; Caron, M; Davey, RJ; Grocke, J; Wray, DS (ACADEMIC PRESS LTD, 2000)
The history of definition of the Aptian-Albian boundary is reviewed with particular reference to the ammonite schemes of Brinkmann (1937), Breistroffer (1947), Casey (1961a, 1996, 1999), Kemper (1982), Owen (1996, 1999), and Ruffell & Owen (1995). The classic sequence in the Hannover area of Germany described by Brinkmann (1937) is reviewed in the light of subsequent work. The definition of the base of the Albian Stage at the first occurrence of the ammonite Proleymeriella schrammeni (Jacob, 1907) is rejected as it can only be recognised over a limited area near Hannover; no more widely recognised secondary markers have been documented, and there is no permanent section at the present rime.An alternative Aptian-Albian boundary, defined by the first occurrence of the ammonite Leymeriella (L.) tardefurcata (d'Orbigny, 1841) in the expanded Marnes Bleues section at Tartonne, Alpes-de-Haute-Provence, France, is suggested.The palynomorph, coccolith, planktonic foraminiferan, ammonite, and inoceramid bivalve sequence, organic and inorganic carbon, trace, rare earth, and major element record, oxygen and carbon isotope sequence, and strontium isotope data are presented for sections at the Col de Pre-Guittard, Arnayon (Drome), and Tartonne (Alpes-de-Haute-Provence) and described in detail. The Pre-Guittard section, considered as a candidate Global Boundary Stratotype Section (GSS) for the base of the Albian Stage at the Second International Symposium on Cretaceous Stage Boundaries held in Brussels in September 1995, provides a standard section for the boundary interval in SE France. It is, however, unsuitable as a GSS, as there is a hiatus at the critical level in the section. In contrast, the Tartonne section is a potential GSS. The Boundary Point for the base of the Albian Stage suggested here is the first criterion proposed at Brussels: the first appearance of the ammonite Leymeriella (L.) tardefurcata at the base of the Niveau Paquier within the expanded Marnes Bleues sequence. The first appearance is only 60 cm above the last record of its presumed ancestor, L. (L.) germanica Casey, 1957. So defined, the boundary lies within the Prediscosphaera columnata Nannofossil (NF) Zone NC/CC8, and the planktonic foraminiferal Hedbergella planispira Partial Range Zone.There is no major or trace element event associated with the proposed boundary, nor is there any distinctive oxygen or carbon isotopic signal. Strontium isotope data from the Tartonne section are compatible with those elsewhere in the basin, and show that the base of the Albian, defined by the first appearance of L. (L.) taudefurcata corresponds to an Sr-87/Sr-86 ratio of 0.707339 +/- 2.Systematic sections deal with a new palynomorph, calcareous nannofossils and ammonites; full range data and taxonomic indices are given for the first two groups. (C) 2000 Academic Press.